2017
DOI: 10.1021/acs.nanolett.7b00004
|View full text |Cite
|
Sign up to set email alerts
|

Simple-Cubic Carbon Frameworks with Atomically Dispersed Iron Dopants toward High-Efficiency Oxygen Reduction

Abstract: Iron and nitrogen codoped carbons (Fe-N-C) have attracted increasingly greater attention as electrocatalysts for oxygen reduction reaction (ORR). Although challenging, the synthesis of Fe-N-C catalysts with highly dispersed and fully exposed active sites is of critical importance for improving the ORR activity. Here, we report a new type of graphitic Fe-N-C catalysts featuring numerous Fe single atoms anchored on a three-dimensional simple-cubic carbon framework. The Fe-N-C catalyst, derived from self-assemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 42 publications
4
108
0
Order By: Relevance
“…It is well known that cyanate and thiocyanate anions coordinate strongly to metals, and consequently can passivates active sites. Thus, it has been shown that the introduction of CN − ions on Fe 1 /N‐doped C or Co 1 /N‐doped C catalysts is detrimental to their performances in ORR, demonstrating the activity of these SAC ,. Theoretical calculations have confirmed that FeN 4 sites present in nitrogen‐doped carbon materials can act as very efficient catalytic sites for oxygen adsorption and O=O bond cleavage, with performances reaching the ones of platinum ,.…”
Section: Catalysis With Single Atom Catalysts On Carbon‐based Materialsmentioning
confidence: 97%
“…It is well known that cyanate and thiocyanate anions coordinate strongly to metals, and consequently can passivates active sites. Thus, it has been shown that the introduction of CN − ions on Fe 1 /N‐doped C or Co 1 /N‐doped C catalysts is detrimental to their performances in ORR, demonstrating the activity of these SAC ,. Theoretical calculations have confirmed that FeN 4 sites present in nitrogen‐doped carbon materials can act as very efficient catalytic sites for oxygen adsorption and O=O bond cleavage, with performances reaching the ones of platinum ,.…”
Section: Catalysis With Single Atom Catalysts On Carbon‐based Materialsmentioning
confidence: 97%
“…Nowadays, one of the most promising candidates to replace PMs as ORR catalyst is single‐atom Fe embedded nitrogen‐doped carbon (Fe–N–C), where FeNx moieties formed by coordination of single‐atom Fe with nitrogen embedded in carbon matrix are regarded as active sites for ORR . However, due to the thermodynamical instability, single‐atom Fe is prone to migration and agglomeration into nanoparticles during pyrolysis, resulting in lower utilization of metal species, decrement of FeN x active site, and thereby poor catalyst performance .…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the loading of single atoms, many research groups have improved the pyrolysis process by the substitution of precursors . For instance, atomically dispersed Fe‐N‐C was prepared by using the Fe‐decorated 3D simple‐cubic carbon frameworks as the precursor . As another example, the pyrolysis of Zn/Co bimetallic metal–organic frameworks (MOF) led to the formation of single‐atom Co‐N‐C species .…”
Section: Introductionmentioning
confidence: 99%